Thermite assisted synthesis of ZrB2 and ZrB2–SiC through B4C reduction of ZrO2 and ZrSiO4 in air - R. V. Krishnarao; R. Sankarasubramanian (Journal of Advanced Ceramics, 2017)
Abstract ZrB2 and ZrB2–SiC powders have been produced by reducing ZrO2 and ZrSiO4 with B4C without using any furnace. Magnesium was added to the mixtures of (ZrO2+B4C) and (ZrSiO4+B4C). The reaction has been assisted by a floral thermite packed around the compacts. By introducing elemental Si into (ZrO2+B4C) mixture, composite powders of ZrB2–SiC formed. After leaching out MgO with suitable HCl water solution, the product was analysed by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The effect of Si, B4C, and Mg on the extent of formation of ZrB2, ZrB2–SiC, and other phases has been studied. Formation of nano-sized ZrB2 and ZrB2–SiC composite powders was identified. The adaptability of the process for bulk production was examined.